Cell recovery during segmental intestinal perfusion in healthy subjects and patients with Crohn's disease. Issue 2 (February 1991) - Ahrenstedt, O; Knutson, F; Knutson, L; Krog, M; Sjöberg, O; Hällgren, R
Abstract : The recovery of cells arising from small intestinal mucosa alone was studied during continuous perfusion of a closed segment of jejunum. The perfusion technique minimised the contamination of the perfused segment with, for example, proteolytic enzymes from pancreas, allowing recovery of viable cells. The use of hyaluronidase in the perfusion fluid increased the recovery of cells fivefold, the median recovery being 8 x 10(6) cells. The cells were analysed with monoclonal antibodies and flow cytometry. Nearly all cells (98-99%) recovered during perfusion of healthy control subjects and patients with Crohn's disease were epithelial cells. The jejunal cells expressed HLA-DR in similar proportions–around 30%–in patients and control subjects. The ratio between CD4+ and CD8+ lymphocytes was similar (0.2) in control subjects and patients with inactive Crohn's disease but decreased (0.03) in patients with active Crohn's disease in the ileum.